The emerging dimensions of SAARC - Muni, S. D.; Lodhi, Iftikhar A.; National University of Singapore. Institute of South Asian Studies (New Delhi : Foundation Books, 2010)
Papers presented at a series of seminars organized by Institute of South Asian Studies, National University of Singapore.
Includes index.
Keywords: SOUTH ASIAN ASSOCIATION FOR REGIONAL COOPERATION; SOUTH ASIAN COOPERATION; SOUTH ASIA -- ECONOMIC INTEGRATION